Transcriptome Response to Drought, Rehydration and Re-Dehydration in Potato - Chen, Yongkun; Li, Canhui; Yi, Jing; Yang, Yu; Lei, Chunxia; Gong, Ming (International journal of molecular sciences, 2019)
Potato is an important food crop and its production is susceptible to drought. Drought stress in crop growth is usually multiple- or long-term. In this study, the drought tolerant potato landrace Jancko Sisu Yari was treated with drought stress, rehydration and re-dehydration, and RNA-seq was applied to analyze the characteristics of gene regulation during these treatments. The results showed that drought-responsive genes mainly involved photosynthesis, signal transduction, lipid metabolism, sugar metabolism, wax synthesis, cell wall regulation, osmotic adjustment. Potato also can be recovered well in the re-emergence of water through gene regulation. The recovery of rehydration mainly related to patatin, lipid metabolism, sugar metabolism, flavonoids metabolism and detoxification besides the reverse expression of the most of drought-responsive genes. The previous drought stress can produce a positive responsive ability to the subsequent drought by drought hardening. Drought hardening was not only reflected in the drought-responsive genes related to the modified structure and cell components, but also in the hardening of gene expression or the “memory” of drought-responsive genes. Abundant genes involved photosynthesis, signal transduction, sugar metabolism, protease and protease inhibitors, flavonoids metabolism, transporters and transcription factors were subject to drought hardening or memorized drought in potato.